Batalia „szklanej rury”. Współzawodnictwo „starego” i „nowego” w debacie wokół doświadczeń z próżnią z 1647 roku - Kołos, Anna (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The article addresses the issue of one of the more intense and captivating European scientific disputes, likewise common to Poland, in the era of the seventeenth-century transformation of knowledge formation, which centered around the possibility of the existence of vacuum, and which culminated in 1647. The fundamental aim of the article comes down to an attempt to determine a position in the scientific-cognitive debate, from which the pro and anti-Polish and European representatives of The Republic of Letters (Respublica literaria) could voice their opinions. In the course of the analysis of the mid-seventeenth century scientific discourse, the reflections of Valeriano Magni, Torricelli, Jan Brożek, Wojciech Wijuk Kojałowicz, Blaise Pascal, Giovanni Elefantuzzi, Jacob Pierius, and Pierre Guiffart are subjected to close scrutiny. From the perspective of contextualism in the history of science, experiments demonstrating the existence of vacuum are perceived as anomalies that fall into the crisis of normal science, largely based on Aristotle’s physics. The conflict between the old and the new is not, however, presented as a battle of progression with epigonism, but merely as a contest between opposing individual views and the concept of science, which before the formation of the new paradigm was accompanied by ambiguous verification criteria.